Refractive outcomes and optical quality after implantation of posterior chamber phakic implantable collamer lens with a central hole (ICL V4c) - Miao, Huamao (BMC Ophthalmol, 2018)
BACKGROUND: To investigate refractive outcomes and optical quality after implantation of posterior chamber phakic implantable collamer lens with a central hole (ICL V4c) to correct high myopia. METHODS: Sixty seven eyes of 38 patients who underwent ICL V4c implantation were enrolled. The mean preoperative spherical equivalent (SE) was − 12.44 ± 3.15 D (range: − 6.63 to − 20.50 D). The refractive outcomes and optical quality of the eyes at postoperative 1 and 3 months were evaluated and compared. RESULTS: At 3 months postoperatively, the mean safety and efficacy indexes were 1.33 ± 0.22 and 1.14 ± 0.23, respectively. The mean SE was − 0.32 ± 0.52 D; no patient lost 1 or more lines of corrected distance visual acuity (CDVA), 13% remained unchanged, 45% gained 1 line and 42% gained 2 or more lines. The mean modulation transfer function cutoff frequency (MTF(cutoff)), Strehl in two dimensions ratio, and objective scatter index (OSI) were 38.20 ± 9.96 cycles per degree, 0.21 ± 0.06, and 1.00 ± 0.73, respectively. No significant difference was found in any of the above parameters (P > 0.05) between 1 and 3 months. The postoperative intraocular pressure (IOP) did not change when compared with preoperative values (P > 0.05). CONCLUSIONS: ICL V4c implantation is a safe, effective, and stable solution for high myopia. Patients will acquire high and stable postoperative optical quality. ICL V4c implantation has little influence on IOP.